The influence of fatiguing exercise on Sport Concussion Assessment Tool (SCAT) scoring in a female pediatric population. Issue 4 (1st October 2020) - Billeck, Jeffrey; Peeler, Jason
ABSTRACT: There is currently a lack of information available about the effect that exercise fatigue may have on Child Sport Concussion Assessment Tool (SCAT) scoring in a pediatric population. Objective : The goal of this study was to examine the influence of a fatiguing bout of aerobic exercise on Child Sport Concussion Assessment Tool (SCAT) scoring in an adolescent female sporting population. Methods : A prospective, observational-based, test-retest study design was used to collect Child SCAT data from thirty healthy 9–12 year old physically active females during two testing sessions that occurred a minimum of 7 days apart. Within each testing session, each child completed a fatiguing bout of aerobic exercise, and the Child SCAT was administered: (1). Pre-exercise and (2). Post-exercise. Parametric and non-parametric testing was used to compare aerobic exercise test results and pre- vs. post-exercise Child SCAT data. Test-retest reliability was evaluated using intra-class correlation coefficient (ICC 3, 1) analysis. Results : No significantly differences were noted between pre- and post-exercise Child SCAT data during either test day. ICC values suggested that a majority of the individual components of the Child SCAT demonstrated poor test-retest reliability. Conclusion : Clinicians using the Child SCAT as a sideline assessment tool during youth sport should have confidence that individual component scores are uninfluenced by aerobic exercise completed immediately prior to assessment. But, clinicians should also be cautioned against using Child SCAT data from consecutive testing days when making decisions about patient recovery and return-to-sport timelines.